Analysis and Economic Substantiation of the Main Disadvantages of the State Regulation Process of the Construction Industry as a Guarantee of State Building and Architectural Control Improvement (Economics and region, 2018)
The article deals with the concept of state regulation of the construction industry. It is analyzed and economically substantiated the main disadvantages of the process of state regulation of the construction industry. The ways of improvement of state building-architectural control are investigated and prospects of development of construction industry are determined
Keywords: state regulation of the construction industry; state building and architectural control; categories of complexity of construction objects; levels of responsibility for construction